Structural Changes of Intermetallic Catalysts under Reaction Conditions. Issue 8 (22nd June 2021) - Li, Xiao; Zhao, Jianxiong; Su, Dong
Abstract : Intermetallics or ordered intermetallic alloys have received more and more attention for the applications of catalysis. Under practical reaction conditions, their atomic arrangements as well as chemical compositions can undergo diverse changes, including reshaping, segregation, disordering, sintering, oxidation, and leaching. These changes directly related to their stability are of great importance for their performances. Herein, the research advances of the structure–performance correlations of intermetallic catalysts, especially on how the structural changes modify their catalytic activity, are reviewed. First, the crystal and electronic structure as well as characterization techniques are introduced. Afterward, the changes of structures under typical reaction conditions by highlighting the underlying mechanisms are discussed. Then, strategies for optimizing the structures are surveyed. Finally, the challenges and perspectives by highlighting the importance of the utilization of in situ techniques are presented. Abstract : Herein, research advances of the structure−performance correlations of intermetallic catalysts are summarized by highlighting the importance of in situ techniques utilization. The structural optimization strategies and current technical challenges are discussed.